Community Education and its Role in Promoting Smart Cities within a Rapidly Changing Technological Environment - Wamaungo, Abdu Juma; Kamil, Mustofa (JENTRE, 2024)
This study explores the role of community education in smart city development within the Indonesian context. The purpose is to understand urban residents' perceptions, attitudes, and barriers toward technology and smart city initiatives and evaluate the effectiveness of current community education programs. A cross-sectional research design was employed, involving surveys and interviews with residents from cities participating in Indonesia's 'Towards 100 Smart Cities' initiative. Thematic and statistical analyses were conducted to analyze the data collected. The findings reveal a mix of optimism and concerns among respondents regarding technology and smart city initiatives, highlighting the importance of addressing privacy, security, and inclusivity issues. While current community education programs effectively raise awareness about smart city concepts, gaps in accessibility and inclusivity persist, suggesting the need for targeted interventions. The study's novelty lies in its contextualized approach to understanding smart city development within Indonesia's diverse urban landscape. It provides practical insights for policymakers and urban planners, emphasizing the importance of community education in promoting inclusive and participatory smart city development. The study contributes to the growing literature on smart city development by offering valuable insights and recommendations for advancing sustainable and equitable urban development in Indonesia and beyond.